An Experimental Investigation of Wage Taxation and Unemployment in Closed and Open Economies - Arno Riedl; Frans van Winden (Tinbergen Institute, 2000)
We investigate experimentally the economic effects of wage taxation to finance unemployment benefits for a closed economy and an international economy. The main findings are the following. (i) There is clear evidence of a vicious circle in the dynamic interaction between the wage tax and unemployment. (ii) Employment is boosted by budget deficits but subsequent tax rate adjustments to balance the budget lead to employment levels substantially lower than theoretically predicted. (iii) A sales risk for producers due to price uncertainty on output markets appears to cause a downward pressure on factor employment. For labor the wage tax exacerbates this adverse effect.
Keywords: C90; D50; E24; F41; 330; Experiments; international economics; wage taxation; unemployment; Lohnsteuer; Arbeitslosigkeit; Offene Volkswirtschaft; Test; Theorie